2017
DOI: 10.2903/j.efsa.2017.4665
|View full text |Cite
|
Sign up to set email alerts
|

Risk for the development of Antimicrobial Resistance (AMR) due to feeding of calves with milk containing residues of antibiotics

Abstract: EFSA was requested to: 1) assess the risk for the development of antimicrobial resistance (AMR) due to feeding on farm of calves with colostrum potentially containing residues of antibiotics; 2) assess the risk for the development of AMR due to feeding on farm of calves with milk of cows treated during lactation with an antibiotic and milked during the withdrawal period, and 3) propose possible options to mitigate the risk for the development of AMR derived from such practices. Treatment of dairy cows during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 162 publications
(358 reference statements)
1
54
0
Order By: Relevance
“…Then, right after the last milking, intra-mammary injection of antibiotic was applied to cow udder through canal teat, followed by application of teat sealant, which simulates the keratin plug, providing a physical barrier to bacterial invasion and preventing milk leakage. DCT can eliminate existing IMI and prevent new infection during dry period; thus, a dry cow tube consists of long persisting antibiotics, as they can deliver better cure rates [ 66 , 67 ]. An ideal treatment should be long enough to cure subclinical mastitis and short enough not to cause antibiotic resistance once the cow has calved.…”
Section: Bovine Mastitis Control and Treatmentmentioning
confidence: 99%
“…Then, right after the last milking, intra-mammary injection of antibiotic was applied to cow udder through canal teat, followed by application of teat sealant, which simulates the keratin plug, providing a physical barrier to bacterial invasion and preventing milk leakage. DCT can eliminate existing IMI and prevent new infection during dry period; thus, a dry cow tube consists of long persisting antibiotics, as they can deliver better cure rates [ 66 , 67 ]. An ideal treatment should be long enough to cure subclinical mastitis and short enough not to cause antibiotic resistance once the cow has calved.…”
Section: Bovine Mastitis Control and Treatmentmentioning
confidence: 99%
“…On most dairy farms in the world calves are either fed waste whole milk or milk replacers (MR). The waste milk encompasses milk from fresh cows and those cows that are undergoing treatment with antibiotics [7]. Furthermore, the waste milk may contain a high amount of somatic cell counts and pathogenic microorganisms [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The waste milk encompasses milk from fresh cows and those cows that are undergoing treatment with antibiotics [7]. Furthermore, the waste milk may contain a high amount of somatic cell counts and pathogenic microorganisms [7,8]. Since the antibiotics can be passed through milk, calves fed on milk from cows undergoing treatment are likely to consume a substantive amount of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent research has also shown that feeding WM to calves impacts the development of the enteric microbiota of calves, when compared to calves fed whole milk without antimicrobial drug residues [19]. However WM is not always used as a feed source, and a recent questionnaire by the European Food Safety Authority (EFSA) Panel on Biological Hazards (BIOHAZ) showed that the disposal of WM when not fed to animals in countries in the European Union included incineration, use as an organic fertilizer, mixing in manure and spreading on land without processing, and composting [20]. These alternative approaches for disposal of waste milk could also result in selection of antimicrobial resistance in the environment, and therefore development of more effective methods for removing the undesired effects of antimicrobial residues in waste milk before disposal would be beneficial.…”
Section: Discussionmentioning
confidence: 99%